Case Study of Polyvinylidene Fluoride Doping by Carbon Nanotubes - Kaspar, Pavel; Sobola, Dinara; Částková, Klára; Dallaev, Rashid; Šťastná, Eva; Sedlák, Petr; Knápek, Alexandr; Trčka, Tomáš; Holcman, Vladimír (Materials (Basel, Switzerland), 2021)
Modern material science often makes use of polyvinylidene fluoride thin films because of various properties, like a high thermal and chemical stability, or a ferroelectric, pyroelectric and piezoelectric activity. Fibers of this polymer material are, on the other hand, much less explored due to various issues presented by the fibrous form. By introducing carbon nanotubes via electrospinning, it is possible to affect the chemical and electrical properties of the resulting composite. In the case of this paper, the focus was on the further improvement of interesting polyvinylidene fluoride properties by incorporating carbon nanotubes, such as changing the concentration of crystalline phases and the resulting increase of the dielectric constant and conductivity. These changes in properties have been explored by several methods that focused on a structural, chemical and electrical point of view. The resulting obtained data have been documented to create a basis for further research and to increase the overall understanding of the properties and usability of polyvinylidene fluoride fiber composites.
Keywords: polyvinylidene fluoride; dielectric constant; crystalline phases; carbon nanotubes